Multiple Colors Making System Using PLC - lubna Farhi; zain Anwar Ali; Saud Zia (Sir Syed University Research Journal of Engineering and Technology)
This paper presents an automated multiple color making system. The various stages of work operations included in the adaptation of manually operated color mixing systems towards fully automated multiple colors making system. The proposed system can extract color features of an image and returns the intensities of Red, Green and Blue colors for a specified pixel in the given image. Since RGB Color Model is used for digital communications like televisions and computer monitors, and CMYK Color Model is used for printing and painting. So, for mixing purpose; the intensities of RGB are then converted into the intensities of Cyan, Magenta, Yellow and Black colors which then further converted into the form of electrical signals. Generally, from three primary colors CMY, a wide range of colors will be made with different proportions. The electrical signals will then be transmitted serially to our Logic Controller for mixing process, that sense the level of primary colors to be mixed and then mix colors proportionally in a container accordingly up to a fixed level in order to make different multiple colors of fixed quantity.  Simulation results shows that the proposed methodology removes the chances like variation in quantity or inaccuracy which happened with the manually color sensing and mixing. It reduces the labor efforts and makes 7% more accurate with minimum error and achieve good retrieval performance.